PENGARUH FEE BASED INCOME, COST INEFFICIENCY, CAR, LDR, DAN FIRM SIZE TERHADAP RISIKO KEBANGKRUTAN (Studi pada Bank Umum Konvensional di Indonesia yang Terdaftar di BEI Periode 2014-2018) - Sari, Dwi Kamilah; Mawardi, Wisnu (Diponegoro Journal of Management, 2020)
The existence of a gap phenomenon in the banking financial ratios that experiencedfluctuations during the 2014-2018 period and the existence of a research gap based onprevious research that still shows inconsistencies in results, and differences in samplingyears form the basis of research on the factors affecting bankruptcy risk. The aims of the study was to determined the effect of fee-based income, costinefficiency, CAR, LDR, and firm size on the bankruptcy risk of Conventional CommercialBanks listed on the IDX. The bankruptcy risk is measured by the Altman Z’-Scorecalculation method. The sample used is conventional commercial banks listed in the Indonesia StockExchange (IDX) during the 2014-2018 period, with a total sample of 35 banks through apurposive sampling method. This study uses multiple linear regression analysis with theIBM SPSS Statistics version 23 program. Before going through the hypothesis testingstage, all data in this study have been declared free from the classical assumption test. The result of this study indicates that the fee-based income, CAR, and LDR variablehas a significant negative effect on the bankruptcy risk variable, the cost inefficiencyvariable has a significant positive effect on the bankruptcy risk variable. Furthermore,both the firm size variable do not effect the bankruptcy risk variable. For the adjusted Rsquare value in this study, the number appears 0.441, which means that the independentvariables in this study can explain the variation of the dependent variable by 44.1%, andthe rest variation is explained by other variables outside the independent variables of thisstudy.